(untitled) (Journal of history, 2019)
This paper compares cultural reading of the Kazakh women’ status from the point of view of the Kazakh traditional culture and Russian officials and scholars’ European view. Authors had raised question about value of different editions of the Kazakh’s customary law on the basis of the influences of postmodern theory on historical research and primary sources interpretation. Authors had concluded about rewriting of previous historiography clichés, when the women’s status had been evaluated only from European cultural norms. Practical implementations of the Adat norms in Kazakh society were more variable, than it was fixed by Russian officials. Furthermore we shouldn’t forget women’s role in Kazakhhousehold and peculiarities of Muslim cult on Kazah’s ordinary life. Thus in orders to more deeply investigate this issue we need using more folklore and ethnographic sources. They allow us to reconstruct a more complete picture of gender roles in the Kazakh society.